Strategy: An International Perspective. - Wit, Bob de; Meyer, Ron (Andover : Cengage Learning, 2015)
In this book, the fundamental differences of opinion within strategic management are not ignored or smoothed over. The authors carefully guide the students through the many, often conflicting, perspectives in the field of strategy, in order to help them become true stategic thinkers.
Keywords: Strategic planning; Business planning